The Knowledge/Power Dilemma and the Myth of the Supermother: a Critique of the Innocent Owner Defense in Narcotics Forfeiture of the Family Home - Morrison, Mairi N. (Columbia Journal of Gender and Law, 1997)
This article arises out of a “narcotics forfeiture defense I handled while a student attorney at the University of Baltimore Housing Law Clinic. Our forfeiture claimant, Celia Darby, was a 55-year-old black woman who had spent most of her life at 1508 North Eden Street, a tiny rowhouse in East Baltimore. She had grown up there, and raised five male children there (burying her oldest the month before we met). When she came to us, she was raising the next generation of the extended family of which she was the center. Had the forfeiture been successful, Ms. Darby ‘s house would have been the first in Baltimore to be taken under Maryland’s Asset Forfeiture Act, legislation which had recently been amended in emulation of the Federal Civil Forfeiture Statute to allow the forfeiture of real property, including the family home. The federal statute provided for the forfeiture of property “used to facilitate” the commission of a narcotics felony. Prosecution under Maryland’s Asset Forfeiture Act required that the home be “used in connection” with a violation of one offive enumerated narcotics offenses, including a crime called “Maintaining a Common Nuisance,” which is a felony in Maryland.